Digit salvage therapy with integrated Chinese and Western medicine: report of case series - Cui, Jiaming; Wang, Hanbo; Yao, Yanlong; Zong, Junwei; Gong, Ying; Sun, Ran; Song, Mingzhi (Frontiers in Medicine, 2025)
BackgroundFinger or toe trauma is a common orthopedic disease. However, the digit salvage treatment method for patients with severe tissue necrosis or infection is very limited.MethodsFive retrospective cases with typical lesions received our integrated traditional Chinese and Western medicine digit salvage therapy. These cases were with necrosis and defect or osteomyelitis. According to the patient’s different lesion characteristics, we carried out the integrated treatment of traditional Chinese and Western medicine including nibbling debridement, negative pressure wound treatment (NPWT), moisture burn ointment (MEBO), rehabilitation exercise and common surgical techniques.ResultsWe considered that precarious alive tissue (PAT) in the residual tissue of the lesion area was very important, especially for promoting tissue regeneration and repairing defects. By nibbling debridement, PAT can be accurately identified. NPWT could protect wound, control infection and fully absorpt the effusion. MEBO was used for dressing changes. While rehabilitation exercise is very important to promote the function recovery. Additionally, bone drilling, skin-grafting and immobilization were also used in different cases. The affected finger or toe healed completely during 1.5–18 months. All patients restored the movement function of the adjacent joints in the lesion area. There was no recurrence of infection or complaint of pain.ConclusionTherefore, traditional Chinese and Western medicine digit salvage therapy may offer an alternative to amputation in select cases. However, further research with larger sample sizes and controlled trials are still needed before wide application of this therapy.